2019
DOI: 10.1111/sms.13383
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a multicomponent physical activity intervention on cognitive performance: The MOVI‐KIDS study

Abstract: Introduction:This study examined the impact of a multicomponent physical activity (PA) intervention (MOVI-KIDS) on improving cognition in schoolchildren. This paper also analyzed the mediator role of motor fitness between MOVI-KIDS and cognition. Methods: Propensity score analysis of data from a cluster randomized controlled trial (MOVI-KIDS study). This analysis including 240 5-7 years old children from nine schools in the provinces of Cuenca and Ciudad Real, Spain. MOVI-KIDS program consisted of: (a) three w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 49 publications
(78 reference statements)
0
33
0
2
Order By: Relevance
“…53-58 i Downgraded to low quality of evidence due to serious risk of bias (many unrandomized designs and some concerns regarding concealment and blinding), some inconsistency of effects, and some indirectness (intervention types and dosages varied). j Study effects were null, 34,62,[70][71][72][73][74][75] positive, [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89] and mixed. 62,[90][91][92][93][94][95][96][97][98][99][100][101][102][103] academic-related outcomes (n = 4510 participants).…”
Section: Data Synthesismentioning
confidence: 99%
“…53-58 i Downgraded to low quality of evidence due to serious risk of bias (many unrandomized designs and some concerns regarding concealment and blinding), some inconsistency of effects, and some indirectness (intervention types and dosages varied). j Study effects were null, 34,62,[70][71][72][73][74][75] positive, [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89] and mixed. 62,[90][91][92][93][94][95][96][97][98][99][100][101][102][103] academic-related outcomes (n = 4510 participants).…”
Section: Data Synthesismentioning
confidence: 99%
“…Scientific attention is focused not only on fitness level, including muscle strength, cardiorespiratory endurance and motor coordination, but also on fitness benefits [1,2]. Many studies have suggested that physical fitness in youth and cognitive skills in later life are closely related [3][4][5]. It was found that primary schoolchildren with higher fitness skills have an advantage over their peers with lower fitness performance in specific cognitive functions [6,7], which can lead to better academic performance [4,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that outdoor activities have a positive impact on attention and concentration in children [28]; children who spend more time engaged in outdoor activities are better prepared for school [29], they are less frequently overweight or obese [30] and generally present with better cognitive functioning [31]. Similar results were obtained regarding physical activity of children; physical activity was related to better cognitive functioning [32], lower body weight [33] and better motor skills in children [34]. Here we need to take into account age and sex differences in outdoor and physical activities; between the third and the fifth year of age children, on the average spend 10% less time engaged in physical activities with every subsequent year [35] while girls, on the average, spend less time outdoor [36] and engaged in physical activities [37] than do boys.…”
Section: Introductionmentioning
confidence: 61%